Effectiveness and safety of single anti-seizure medication as adjunctive therapy for drug-resistant focal epilepsy based on network meta-analysis - Deng, Nian-Jia; Li, Xin-Yi; Zhang, Zhi-Xin; Xian-Yu, Chen-Yang; Tao, Yu-Ting; Ma, Yu-Tong; Li, Hui-Jun; Gao, Teng-Yu; Liu, Xin; Luo, Jie; Zhang, Chao; Hu, Sheng-Li (Frontiers in Pharmacology, 2025)
ObjectiveTo evaluated the effectiveness and safety of single anti-seizure medication (ASM) when used as adjunctive therapy for drug-resistant focal epilepsy.MethodsWe conducted a comprehensive search of PubMed, EMbase, and the Cochrane Library from their inception until 12 February, 2025, to identify randomized controlled trials (RCTs) meeting our criteria. The trials were analyzed for their use of ASMs in treating drug-resistant focal epilepsy. Inclusion criteria comprised: 1) Participants aged 12 years or older with drug-resistant focal epilepsy; 2) Incorporation of an additional single ASM as an adjunct to the existing antiepileptic treatment regimen; 3) Comparison with placebo or continuation of the original antiepileptic regimen without a new ASM; 4) Primary outcome as a 50% response rate, with safety as a secondary outcome, encompassing dizziness, somnolence, headache, ataxia, diplopia, fatigue, and nausea; and 5) Study design limited to RCTs. The surface under the cumulative ranking curve (SUCRA) was employed to rank the effectiveness and safety of the ASMs.ResultsA total of 53 RCTs involving 17 ASMs as adjunctive therapy and placebo were analyzed. Compared to placebo, the following ASMs demonstrated statistically significant effectiveness in achieving a 50% response rate: brivaracetam (RR = 2.07, 95% CI: 1.53–2.81), cenobamate (RR = 2.12, 95% CI: 1.56–2.88), eslicarbazepine acetate (RR = 1.95, 95% CI: 1.41–2.70), gabapentin (RR = 2.30, 95% CI: 1.76–3.02), lacosamide (RR = 2.22, 95% CI: 1.47–3.35), lamotrigine (RR = 1.55, 95% CI: 1.00–2.40), levetiracetam (RR = 2.43, 95% CI: 1.88–3.15), oxcarbazepine (RR = 3.03, 95% CI: 2.08–4.40), perampanel (RR = 1.72, 95% CI: 1.21–2.44), pregabalin (RR = 2.06, 95% CI: 1.70–2.50), rufinamide (RR = 2.28, 95% CI: 1.20–4.31), tiagabine (RR = 4.07, 95% CI: 2.03–8.18), topiramate (RR = 3.10, 95% CI: 2.44–3.95), vigabatrin (RR = 2.34, 95% CI: 1.58–3.46), and zonisamide (RR = 2.40, 95% CI: 1.76–3.27). Based on SUCRA rankings, tiagabine (92.7%) exhibited the most favorable therapeutic outcome, followed by topiramate (87.3%), oxcarbazepine (83%), and levetiracetam (62.8%). The ASMs with the least favorable therapeutic effects were placebo (1.1%), lamotrigine (17.8%), and perampanel (24.7%).ConclusionThe network meta-analysis revealed topiramate, tiagabine, oxcarbazepine, and levetiracetam as the four most effective adjuvant ASM treatments for drug-resistant focal epilepsy. However, it is noteworthy that topiramate and oxcarbazepine were associated with a higher incidence of somnolence. Additionally, comprehensive safety data for tiagabine and levetiracetam are lacking, necessitating further research. Larger studies are required to solidify these findings and better understand the safety profiles of all involved ASMs.